Investigating Skin Permeation Behavior, Skin Irritation and Anti-Inflammatory Activity of Diclofenac Diethylamine Novel Formulation Prepared using Shea Butter as Absorption Base with Nerolidol as Permeability Enhancer - Aher, Rutuja (Asian Journal of Pharmaceutics (AJP), 2024)
Background: The present investigation was to study the drug permeation of diclofenac diethylamine (DDEA) cream prepared using shea butter as the absorption base and nerolidol as a permeability enhancer and also to evaluate skin irritation and anti-inflammatory study of prepared cream on Wistar rats in comparison with marketed formulation. Materials and Methods: The cream prepared using shea butter and nerolidol was assessed for permeation study through rat skin. The three formulations mainly F0 (without nerolidol), F5 (containing 0.5% nerolidol), and the marketed formulation were assessed for % drug permeation through rat skin along with an estimation of flux and permeability coefficient. A skin irritation study of a placebo, F0, and F5 formulation was carried out on Wistar rats. Anti-inflammatory study of transdermal cream formulation of control, placebo, F0, F5, and marketed formulation was evaluated for anti-inflammatory study on Wistar rat using carrageenan-induced rat paw edema method. Results: The F5 formulation showed enhanced drug permeation as compared to the F0 and marketed formulation. The flux value F5 formulation was found to be 0.3942 ± 0.009 g/cm2/min as compared to F0 and marketed formulation which were found to be 0.2789 ± 0.013 g/cm2/min and 0.2730 ± 0.0110 g m/cm2/min, respectively. The permeability coefficient for the F5 formulation was found to be 2.370 × 10-5 m/s as compared to F0 and marketed formulations which were found to be 1.680 × 10-5 and 1.640 × 10-5 m/s, respectively. The F0 and F5 formulations were found to be non-irritant and no edema was observed on its application. F5 formulation showed significant inhibition of edema in rat paw volume induced by carrageenan as compared to control, placebo, Std, and F0 batches. Conclusion: The study demonstrates that the F5 formulation prepared using shea butter as an absorption base and containing 0.5% w/v of nerolidol as a permeability enhancer showed a better permeation of DDEA through rat skin, non-irritant in nature and significant anti-inflammatory activity as compared to F0 and marketed formulation.